Effect of microbial inoculant on the oviposition and completion of life cycle of Chrysomya megacephala (Fabricius) and Chrysomya rufifacies (Macquart) infesting rabbit carcasses: Effect of microbial inoculant on Chrysomya megacephala (Fabricius) and Chrysomya rufifacies (Macquart) - Naji Arafat Mahat; Nur Amalina Omar; Heo Chong Chin; Mohammad Rahim Kamaluddin; Nor Wajihan Muda (Journal of Tropical Life Science, 2023)
This research was conducted to assess the influence of microbial inoculant (EM.1®) on the initial oviposition and developmental pattern of two prevalent necrophagous flies (Chrysomya megacephala and Chrysomya rufifacies) in Malaysia. Nine rabbit carcasses were equally divided into control and two treated groups. The control carcasses were sprayed with deionized water (about 100 mL), whereas the two other treated groups were individually sprayed with two concentrations of EM.1® at 1:500 and 1:100, respectively. Results revealed that the single application of EM.1® on both treated carcasses did not statistically impede oviposition by both necrophagous species, as well as their subsequent developmental patterns (P > 0.05) when compared with that of controls. Therefore, estimating the minimum post-mortem interval (mPMI) using empirical baseline data for the control animal model would remain appropriate for estimating mPMI in cases involving carcasses with a single application of EM.1®